STRATEGI KOMUNIKASI PEMASARAN SHIFT MERCHANDISE DALAM MEMBANGUN BRAND AWARENESS - Farrah Septrina; Indria Angga Dianita (Journal of Management Small and Medium Enterprises (SMEs), 2022)
The phenomenon of Hijrah is familiar in big cities and involves many young people. The Shift Pemuda Hijrah is one of the Islamic movements that formed the phenomenon of hijrah in the city of Bandung. To support its da'wah operational activities, Shift Pemuda Hijrah formed a business unit called Shift Merchandise. Shift Merch is engaged in the apparel sales industry. Shift Merch, which was initiated in 2015 in Bandung and launched into the clothing industry in March 2016. This study aims to determine the marketing communication strategy of Shift Merch in building brand awareness. This study uses an interpretive paradigm with a descriptive qualitative approach. The data in this study were obtained through observation, documentation, literature study and the results of interviews with the Shift Merch branding officer as a key informant, a marketing expert as an expert informant and Shift Merch admin as a supporting informant. The results of this study reveal that there are message strategies and media strategies used by Shift Merch in carrying out marketing communications that are always integrated with Shift Media, because Shift Merch is a measuring tool for indicators of the success of their preaching Shift Pemuda Hijrah. Through its marketing communication medium, namely Instagram, Shift Merch has succeeded in building brand awareness through Shift Media. Suggestions that researchers can give are to add new media channels and build stories on creative messages so that they can build their own brand awareness. Keywords: Marketing Communication, Brand Awareness, Shift Merch